Using Local Wisdom as a Protection from COVID-19 - Natsir, Muhammad; Saragih, Bahagia; Lubis, Tasnim (Tradition and Modernity of Humanity, 2022)
The spread of COVID-19, which is difficult to predict, has caused the community to experience shocks both mentally and psychologically which also affects the social relations of the community down to the lowest level. The culture of gathering in Indonesian society that has become a daily routine has stopped and there is no concern about when it will recover. The cracks for the sake of grazing in our society are beginning to be felt. People began to experience panic anxiety so that government recommendations and religious institutions were ignored by some people with logical defects and put forward emotional sentimentality. In that condition, social capital in synergy with local wisdom can be a solution so that social anxiety and fractures do not occur.